2023
DOI: 10.2478/ceej-2023-0012
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Social Capital and Institutional Environment‘s Impact On the Success of Regional Cluster Policies

Abstract: Cluster policies (CPs) are said to be one of the crucial elements supporting the innovativeness of local and regional economies. However, what drives the success of CPs has not been made fully explicit. We tested the impact of perceived quality and strength of social capital (SC) and the formal institutional environment (FIE) upon CPs. We studied this relationship by applying structural equation modelling to data from quantitative CATI research on members of 20 cluster initiatives from four Polish administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…In turn, these secondary benefits may include improving the quality of life of a society or making it a more attractive place for foreign direct investment in the long term. When comparing this with the outcomes observed by Kwiatkowski et al (2023), who explored the impact of formal institutional environments on the effectiveness of regional cluster policies in 20 Polish clusters and found that cluster coordinators are often institutions from the business environment, one might suggest that such a role could be taken up by companies excelling in ESG practices. Furthermore, improving the quality of life for communities can serve as an example of caring for a broad group of stakeholders, thus perfectly embodying the stakeholder theory (Azmi et al, 2021;Jo & Harjoto, 2011;Ruf et al, 2001).…”
Section: Conclusion and Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In turn, these secondary benefits may include improving the quality of life of a society or making it a more attractive place for foreign direct investment in the long term. When comparing this with the outcomes observed by Kwiatkowski et al (2023), who explored the impact of formal institutional environments on the effectiveness of regional cluster policies in 20 Polish clusters and found that cluster coordinators are often institutions from the business environment, one might suggest that such a role could be taken up by companies excelling in ESG practices. Furthermore, improving the quality of life for communities can serve as an example of caring for a broad group of stakeholders, thus perfectly embodying the stakeholder theory (Azmi et al, 2021;Jo & Harjoto, 2011;Ruf et al, 2001).…”
Section: Conclusion and Discussionmentioning
confidence: 92%
“…Most studies examining the correlation between ESG practices and the worth of companies primarily concentrate on non-financial corporations located in emerging economies. Nevertheless, the level of governance, transparency, and regulatory obligations in emerging markets is comparatively lower than that in industrialised markets (Khanna & Palepu, 2000). These economies are marked by increased uncertainty, and banks in these markets implement anti-cyclical buffers for capital (Bilgin et al, 2021;Moudud-Ul-Huq, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%